High connectivity within restricted distribution range in Pocillopora corals. (2nd April 2021) - Oury, Nicolas; Gélin, Pauline; Magalon, Hélène
Abstract: Aim: Convergence, stasis and plasticity can frequently confound our understanding of species distributions in the seas. Yet delimiting species and understanding population connectivity across marine environments is mandatory for establishing appropriate management of coral reefs, which are experiencing critical declines. We test whether morphospecies from Pocillopora corals found on outer reef slopes are unique species or species complexes, in order to correctly define their respective distributions and consequently to accurately assess their population connectivity. Location: Archipelagos and islands of the Western Indian Ocean and the Southern Pacific (New Caledonia, Tonga, French Polynesia). Taxon: Pocillopora eydouxi / meandrina and Pocillopora verrucosa morphospecies (Scleractinia). Methods: We analysed the 13‐microsatellite genotypes of 4837 colonies from six understudied ecoregions in the southern part of the genus distribution, to first explore the genetic partitioning within morphospecies. We then characterized the spatial distribution of each delimited species and analysed patterns of genetic diversity and connectivity for each species separately. Results: Both morphospecies are complexes of species, each found almost exclusively in the Indian or the Pacific Oceans. Moreover, some of these cryptic species are found in sympatry over their whole distribution, which sometimes was very restricted. However, within each species, genetic diversity and connectivity were relatively high, although some populations were found differentiated for some species, while not for others. Main conclusions: A weak connectivity was found between the Indian and Pacific Oceans, but high connectivity within both oceans, supporting the existence of a barrier impeding gene flow between both ocean basins in Pocillopora . Although constrained by the same geography and current patterns, some sympatric species present different connectivity patterns, demonstrating the importance of multi‐species connectivity models to set up appropriate management plans.